Self-assessed intelligence, personality and measured IQ: phenotypic and genetic associations - Bratko, Denis (Array, 2012)
Phenotypic and genetic associations between self-assessed intelligence, personality and measured IQ were explored using 732 Croatian twins (15-22 years old). Data was collected on cognitive ability, self-assessed intelligence (SAI), and Five-Factor Model personality traits via mail. Significant phenotypic associations were found: measured IQ correlated positively with self-assessed intelligence and Openness, and negatively with Neuroticism and Extraversion. Also self-assessed intelligence correlated positively with Openness. Subsequent bivariate genetic analyses revealed that these phenotypic associations were mainly due to overlapping genetic influences. Multivariate analyses indicated that around 20% of IQ variance could be explained by SAI and personality traits (Neuroticism, Extraversion, Openness). In combination with other recent findings from behavior genetics, this result supports the idea of pleiotropy and generalist genes.